Association between spinal cord compression ratio in magnetic resonance imaging, initial neurological status, and recovery after ventral slot in 57 dogs with cervical disc extrusion - Bach, Fernando Swiech; Mai, Wilfried; Weber, Luiz Felipe Silva; Villanova Junior, José Ademar; Bianchi de Oliveira, Leonardo; Montiani-Ferreira, Fabiano (Frontiers in Veterinary Science, 2023)
This retrospective, unblinded, single rater study evaluated images obtained from magnetic resonance imaging (MRI) of dogs with cervical intervertebral disc extrusion before being submitted to ventral slot decompression (VSD). Dogs were re-evaluated systematically at 10 and 30 days after VSD. The objectives of this study were to investigate the associations between the following parameters: 1) The maximal spinal cord compression ratio (SCCR) as seen on transverse MRI and pre-surgical neurological status (NS) grade; we hypothesized that dogs with greater SCCR will have worse pre-surgical NS grade at presentation; 2) Pre-surgical NS grade and postoperative recovery; we hypothesized that worse pre-surgical NS grade will be associated with longer postoperative recovery time; 3) SCCR and postoperative recovery; we hypothesized that dogs with higher SCCR will have longer recovery time; 4) Location of extrusion (cranial vs caudal) and initial NS grade and outcomes; we hypothesized that caudal cervical extrusion will have worse NS grade and longer time to recovery; 5) Longitudinal extension of ventral CSF signal loss on HASTE pulse sequence and NS grade and time to recovery; we hypothesized that dogs with longer HASTE CSF attenuation will have higher NS grade and longer time to recovery. There was no significant association between SCCR and NS grade, suggesting that this relationship in the cervical region is similar to what is observed in the thoracolumbar region, rejecting our first hypothesis. There was a significant difference between ambulatory tetraparesis dogs versus non-ambulatory tetraparesis dogs regarding complete recovery at 10 days: dogs with NS grade 1, 2 or 3 overall recovered faster than dogs with NS grade 4. However, there was no significant difference between these groups regarding complete recovery at 30 days, thereby accepting our second hypothesis at 10 days and rejecting it at 30 days. There was no correlation between SCCR and recovery time, rejecting our third hypothesis. Caudal cervical extrusion did not show higher NS grade or longer recovery time than cranial extrusion, rejecting our fourth hypothesis. CSF attenuation length ratio on HASTE images was not significantly correlated with NS grade but weakly correlate with post-surgical recovery time, partially accepting our fifth hypothesis.